ADVANTAGES OF USING REMOTE BANKING SERVICES IN COMMERCIAL BANKS OF UZBEKISTAN - Karachayeva Mashkhura Valijonovna (American Journals, 2023)
This article examines the importance of remote banking services in banking, the channels of their provision and the possibilities of further expansion. The state of development of remote banking services in the practice of commercial banks of Uzbekistan was analyzed on the basis of collected statistical data, and opinions of foreign and local scientists on this topic were also presented. Also, proposals and recommendations were made regarding the further expansion of the types of remote services of the commercial banks of our country.
Keywords: economy, banking sector, commercial banks, remote banking system and services, information technologies, digitization processes